PENGARUH MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN TERHADAP TINGKAT KEPATUHAN PENGUSAHA KENA PAJAK PADA LOKASI PUSAT BISNIS dan PERDAGANGAN DI KAWASAN TANJUNG PERAK SURABAYA - Tjendraputra, Haiwei; Purwanto, Marini; Mulia, Teodora Winda (Jurnal Akuntansi Kontemporer, 2014)
Tax is the main source of State revenues that are used for government financing and development. However, nowadays many cases occurred in the field of taxation in terms of compliance related tax payments. Not only the State apparatus that acts to wayward against the payment of taxes, even personal taxpayers is also not uncommon for tax evasion. One of the ways that can be done to minimize such cases is through increased taxpayer compliance. This research aims to analyze the influence of modernization of tax administration sys-tem of the level of compliance of employers taxable. The independent variables are taken is the modernization of tax administration sys-tem which includes the organizational structure, service quality, facilities services using information technology, and the code of con-duct. The respondents of the research is that there is a taxable entrepreneur in the city of Surabaya. Sampling method using snowball sampling. Research on the data analysis techniques using multiple linear regression test, and the data obtained were processed using the SPSS statistical software. The results of this research indicate that the modernization of organizational structure of taxation and modernizing the service quality has no effect against a compliance level of taxable entrepreneur in the city of Surabaya. Whereas mod-ernization of the facilities services using information technologies and the modernization of the code of conduct compliance rate to taxa-ble entrepreneur in the city of Surabaya. This indicates that although there has been a renewal of the organizational structure and the quality of service from the tax office would not increase taxable bussinessman compliance.